Global epidemiology of breast cancer based on risk factors: a systematic review - Roheel, Amna; Khan, Aslam; Anwar, Fareeha; Akbar, Zunaira; Akhtar, Muhammad Furqan; Imran Khan, Mohammad; Sohail, Mohammad Farhan; Ahmad, Rizwan (Frontiers in Oncology, 2023)
Background Numerous reviews of the epidemiology and risk factors for breast cancer have been published previously which heighted different directions of breast cancer. Aim The present review examined the likelihood that incidence, prevalence, and particular risk factors might vary by geographic region and possibly by food and cultural practices as well. Methods A systematic review (2017-2022) was conducted following Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines, reporting on epidemiological and risk factor reports from different world regions. Medical Subject Heading (MeSH) terms: “Breast neoplasm” “AND” country terms such as “Pakistan/epidemiology”, “India/epidemiology”, “North America/epidemiology”, “South Africa/epidemiology” were used to retrieve 2068 articles from PubMed. After applying inclusion and exclusion terms, 49 papers were selected for systematic review. Results Results of selected articles were summarized based on risk factors, world regions and study type. Risk factors were classified into five categories: demographic, genetic and lifestyle risk factors varied among countries. This review article covers a variety of topics, including regions, main findings, and associated risk factors such as genetic factors, and lifestyle. Several studies revealed that lifestyle choices including diet and exercise could affect a person’s chance of developing breast cancer. Breast cancer risk has also been linked to genetic variables, including DNA repair gene polymorphisms and mutations in the breast cancer gene (BRCA). It has been found that most of the genetic variability links to the population of Asia while the cause of breast cancer due to lifestyle modifications has been found in American and British people, indicating that demographic, genetic, and, lifestyle risk factors varied among countries. Conclusion There are many risk factors for breast cancer, which vary in their importance depending on the world region. However, further investigation is required to better comprehend the particular causes of breast cancer in these areas as well as to create efficient prevention and treatment plans that cater to the local population.